Psychological and Pedagogical Bases for Monitoring and Evaluating the Activities of Students in the Lessons of the Russian Language - Umarova Dilfuza Mamatkulovna; Allayarova Dilfuza Klichevna (Genius Journals, 2022)
Performing the function of managing the educational and cognitive activity of students, control is not always accompanied by grading. It can act as a way to prepare students for the perception of new material, to identify students' readiness to master knowledge, skills and abilities, to generalize and systematize them. Control has an important educational and developmental value.
Keywords: Level Of Correctness; Volume; Depth; Validity